Determining the interconnection between personality and physical activity on perceived stress in a diverse sample - Courtney, Rena Elizabeth; Schadegg, Mary Josephine; Brice, Patrick; Friedman, Bruce H.; Fanning, Jason (Frontiers in Psychology, 2025)
IntroductionStress is considered an epidemic with far-reaching deleterious impacts across multiple domains while engagement in physical activity (PA), a proven way to reduce perceived stress (PS), remains low. The purpose of this study was to determine whether the Five Factor Model (FFM) personality factors and self-reported PA have independent main effects on PS, and to examine the interaction between PA and personality on PS. We predicted that neuroticism, extraversion, conscientiousness, and PA would predict PS.MethodsA cross-sectional study was conducted. Participants were adults without anxiety disorders who completed online surveys including the IPIP-NEO-120, PSS-10, and IPAQ-Long. An iterative series of linear regressions were used to determine whether personality characteristics and PA were related to PS and to detect interactive effects.ResultsThe final sample included 276 participants who were, on average, mostly non-White (62%), reported moderate level of PS (Mean PSS Total Score = 17.01, SD = 6.74), and reported high levels of PA (Mean Total MET-minutes per week = 2,994.81, SD = 2,620.92). The hypothesis was partially supported such that neuroticism (B = 0.02, p = <0.001) and conscientiousness (B = 0.02, p = <0.001) predicted PS, though PA did not. Only openness to experience demonstrated an interactive effect, with those high in openness to experience and PA tended to have higher PS.DiscussionThis study provides additional support for the relationship between the FFM of personality and PS. Future studies on the connection between PS, personality, and PA may benefit from the use of a combined approach, including both self-report and objective measures of PA.